Designing nickel coatings for water erosion performance: optimisation of grain size and thickness - Gaddavalasa, Nithin Chandra; Lodh, Arijit; Cini, Andrea; Saaran, Vinodhen; Mehmanparast, Ali; Starr, Andrew; Castelluccio, Gustavo M. (Elsevier, 2025)
Metallic coatings are gaining interest as an alternative to classical polymeric layers for erosion damage prevention due to their extended durability and sustainability. However, their implementation requires a thorough understanding of protective potential and reliability. This study explores the use of brush-plated nickel coatings on carbon-fibre reinforced composites to enhance their performance against water erosion. A combination of experimental analysis and computational modeling explores the effect of different coating thickness and properties to withstand water droplet erosion damage. Findings reveal a minimum critical coating thickness around 40 μ m can significantly improve the erosion resistance.
Keywords: 40 Engineering; 4016 Materials Engineering; Mechanical Engineering & Transports; 4005 Civil engineering; 4016 Materials engineering; 4017 Mechanical engineering